2017
DOI: 10.1017/s0950268817002126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anti-hepatitis B surface antibodies among children and adolescents vaccinated in infancy and effect of booster dose administered within a pilot study

Abstract: We determined the prevalence of anti-hepatitis B surface antibodies (anti-HBs) among children and adolescents vaccinated for hepatitis B virus in infancy as part of the routine vaccination programme. A representative serum sample of the Israeli population age 0-19 was tested. In a separate pilot study, a booster dose of hepatitis B vaccine was administered to 31 candidates for national service, who were fully vaccinated in infancy and tested negative for hepatitis B surface antibodies at age 17-19 years and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
5
0
7
Order By: Relevance
“…HBsAg positive children would not receive a booster dose. As one would anticipate, the anti-HBs positive rate was significantly higher in the booster group than in the no-booster group, a finding shown by others 15,16 . There was no statistically significant difference in HBsAg positivity between the two groups.…”
Section: Discussionmentioning
confidence: 52%
“…HBsAg positive children would not receive a booster dose. As one would anticipate, the anti-HBs positive rate was significantly higher in the booster group than in the no-booster group, a finding shown by others 15,16 . There was no statistically significant difference in HBsAg positivity between the two groups.…”
Section: Discussionmentioning
confidence: 52%
“…Upon booster vaccination of 19 individuals without residual antibodies, all but one mounted a robust anamnestic response ( 44 ). By contrast, several studies showed that only 20–30% of adolescents who received primary vaccination in infancy still had protective anti-HBs levels around age 18 ( 45 47 ). The age when primary vaccination is received appears to play an important role in the long-term maintenance of anti-HBs.…”
Section: Discussionmentioning
confidence: 94%
“…Although the seroconversion rate of hepatitis B vaccine is high, long-term studies have shown that the anti-HBs seropositivity ratio to hepatitis B decreases with age. 19 ,20, 21 In a 20-year study by Ni et al, 22 the overall seropositivity rate of anti-HBs in 3332 individuals at 20 years of the HBV vaccination was 55.9%. Kim et al 23 also reported an overall seropositivity rate of 55.8% in the vaccinated children and young adults (1-27 years).…”
Section: Discussionmentioning
confidence: 99%